2004
DOI: 10.1182/blood-2004-03-0897
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase polymorphism (C677T), hyperhomocysteinemia, and risk of ischemic cardiovascular disease and venous thromboembolism: prospective and case-control studies from the Copenhagen City Heart Study

Abstract: Hyperhomocysteinemia is associated with ischemic cardiovascular disease (ICD) and venous thromboembolism (VTE). We tested the hypothesis that methylenetetrahydrofolate reductase (MTHFR) C677T homozygosity with hyperhomocysteinemia is associated with ICD and VTE. First, 9238 randomly selected whites from the general population were followed for 23 years. Second, 2125 whites with ischemic heart disease and 836 whites with ischemic cerebrovascular disease were compared with 7568 controls from the general populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 18 publications
6
74
2
1
Order By: Relevance
“…Several small case-control studies have included simultaneous measurements of MTHFR genotype and plasma homocysteine concentrations in relation to CVD (10 ), but only 1 study, the Copenhagen City Heart Study, was conducted in a prospective manner, although data on gene-diet interactions were not reported (27 ). In accordance with those studies, we found that the T allele was associated with higher plasma homocysteine concentrations.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Several small case-control studies have included simultaneous measurements of MTHFR genotype and plasma homocysteine concentrations in relation to CVD (10 ), but only 1 study, the Copenhagen City Heart Study, was conducted in a prospective manner, although data on gene-diet interactions were not reported (27 ). In accordance with those studies, we found that the T allele was associated with higher plasma homocysteine concentrations.…”
Section: Discussionsupporting
confidence: 77%
“…In accordance with those studies, we found that the T allele was associated with higher plasma homocysteine concentrations. Whereas the case-control studies found mixed results regarding the association of MTHFR homozygosity and CVD risk (10 ), the Copenhagen City Heart Study found no association between MTHFR genotype with incident CVD or venous thromboembolic events (27 ). Another prospective study with 18 years of follow-up in women also found no increased CVD risk associated with the T allele, although homocysteine concentrations were not studied (28 ).…”
Section: Discussionmentioning
confidence: 97%
“…The results from MDR also showed several genetic interactions that were significant after permutation testing. Our findings appear to be of importance and relevant because they implicated involvement of genes, which have been shown previously to be connected with development of atherosclerosis (10,11,14,15,27,30,46). The use of MDR closely reassembles the complex nature and multifactorial base of the disease by evaluating multiple SNPs in an unbiased way.…”
Section: Resultsmentioning
confidence: 98%
“…It was suggested that 4G-deletion polymorphism of the promoter region increases the risk of CVD (22) by removing the extra guanosine base in the binding site, which attenuate the response to the transcription repressor factor and enhance the PAI-1 transcription (22), and hence reduce fibrinolytic activity (38). Several other factors have been implicated in the regulation of the fibrinolytic and thrombotic processes in patient with CVD, among them is the elevated level of homocysteine (15). It has also been shown that that MTHFR 677 polymorphism (C677T, rs1801133) can result in elevated homocysteine levels, which may lead to an increased risk of thrombotic events.…”
Section: Resultsmentioning
confidence: 99%
“…In the prospective study of Frederiksen et al 40 , the Hcy mean concentration was higher in MTHFR 677TT genotype carriers compared to the carriers of other genotypes; however, the MTHFR C677T polymorphism was not associated with ischemic cardiovascular disease or thromboembolism. Similar observations were reported by Huh et al 41 and Yilmaz et al 36 in CAD studies.…”
Section: Discussionmentioning
confidence: 99%